2022
DOI: 10.3390/foods11121698
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Antioxidant Activity of Walnut Oil Using Various Pretreatment and Processing Technologies

Abstract: This study was the first time the effects of pretreatment technology (microwave roasting, MR; oven roasting, OR; steaming roasting, SR) and processing technology (screw pressing, SP; aqueous enzymatic extraction, AEE; subcritical butane extraction, SBE) on the quality (physicochemical properties, phytochemical content, and antioxidant ability) of walnut oil were systematically compared. The results showed that the roasting pretreatment would reduce the lipid yield of walnut oil and SBE (59.53–61.19%) was the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The POV of the RS oil (0.55 mmol/kg) was lower than that of the RP oil (0.63 mmol/kg) ( p < 0.05). Gao et al (2022) also reported that the POVs of walnut oils obtained by subcritical extraction were significantly lower than screw pressing. It was possibly due to the low processing temperature and anaerobic environment in the subcritical extraction equipment which inhibited lipid oxidation.…”
Section: Resultsmentioning
confidence: 95%
“…The POV of the RS oil (0.55 mmol/kg) was lower than that of the RP oil (0.63 mmol/kg) ( p < 0.05). Gao et al (2022) also reported that the POVs of walnut oils obtained by subcritical extraction were significantly lower than screw pressing. It was possibly due to the low processing temperature and anaerobic environment in the subcritical extraction equipment which inhibited lipid oxidation.…”
Section: Resultsmentioning
confidence: 95%
“…The substitution of animal fat by the gelled emulsion elaborated with walnut oil and cocoa bean shell flour improved the nutritional values of burgers because the principal fatty acids found in BWC50 and BWC100 were polyunsaturated fatty acids with values of 360.58 and 495.70 mg g −1 fat, respectively, due to the high linoleic acid (C18:2n-6) and ⊍-linolenic acid (C18:3n-3) content present in walnut oil. 44 In the same way, the saturated fatty acids were reduced with respect to the control sample, thus in BWC50 the reduction achieved was 33.75%, whereas in BWC100 the reduction of saturated fatty acid was 38.88%. The results obtained agreed with those reported in the scientific literature, which indicated that the substitution, in fresh and cooked meat products, of animal fat by gelled emulsion or oleogels elaborated with healthier vegetable oils improved the nutritional quality of this type of meat products.…”
Section: Fatty Acids Profilementioning
confidence: 81%
“…Among monounsaturated fatty acids, oleic acid (C18:1n‐9) represented the highest ( P < 0.05) relative percentage and palmitic acid (C16:0) was the predominant acid ( P < 0.05) within the saturated fatty acids. The substitution of animal fat by the gelled emulsion elaborated with walnut oil and cocoa bean shell flour improved the nutritional values of burgers because the principal fatty acids found in BWC50 and BWC100 were polyunsaturated fatty acids with values of 360.58 and 495.70 mg g −1 fat, respectively, due to the high linoleic acid (C18:2n‐6) and α ‐linolenic acid (C18:3n‐3) content present in walnut oil 44 . In the same way, the saturated fatty acids were reduced with respect to the control sample, thus in BWC50 the reduction achieved was 33.75%, whereas in BWC100 the reduction of saturated fatty acid was 38.88%.…”
Section: Resultsmentioning
confidence: 99%
“…According to Table 1 , the chemical parameters of IPPO, including acid, peroxide, iodine, and saponification values, differed greatly depending on the region. The acid values of IPPO ranged from 0.98 ± 0.02 to 2.25 ± 0.02 mg KOH/g, which was lower than that of sesame oil (3.78 mg KOH/g) [ 29 ] and walnut oil (2.49 mg KOH/g) [ 30 ]. The low acid value indicated that IPPO had strong storage stability, low oil rancidity, and good quality, making it suitable as an edible oil.…”
Section: Resultsmentioning
confidence: 99%